Predictors of academic performance, success and retention amongst undergraduate nursing students: A systematic review - Mthimunye, K.; Daniels, F.M. (South African Journal of Higher Education, 2019)
Background: Unsatisfactory academic performance is a major challenge for universities and schools of nursing globally. Early identification of students who are at risk of unsatisfactory academic performance may assist in decreasing the attrition rate and increasing academic success and progression. Purpose: To review available evidence that determines predictors of academic performance, success and retention amongst undergraduate nursing students. Design: A systematic review of research studies conducted between 2006 and 2016 to determine the predictive validity of factors predicting academic performance, success and retention amongst nursing students. Method: Science Direct, Escohost, BioMed Central, PubMed, SAGE Journals and Directory of Open Access Journals were used to search the literature for studies meeting the inclusion criteria. Studies were assessed for methodological quality using six indicators: selection bias, research design, data collection methods, data source, withdrawals and method of analysis. Findings: Of the 530 studies identified, 17 reached the desired quality and were shortlisted for systematic review. The predictors of academic performance and success were identified from the following categories: (1) student profile characteristics, (2) student affective factors, (3) academic factors, (4) environmental factors, (5) academic outcomes and (6) psychological outcomes. Conclusion: Early identification of at-risk nursing students, and the implementation of remedial action, are fundamental in preventing high attrition rates, and thus promote academic success.